2016
DOI: 10.1007/s10195-016-0433-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematized water content calculation in cartilage using T1-mapping MR estimations: design and validation of a mathematical model

Abstract: BackgroundUp to 80 % of cartilage is water; the rest is collagen fibers and proteoglycans. Magnetic resonance (MR) T1-weighted measurements can be employed to calculate the water content of a tissue using T1 mapping. In this study, a method that translates T1 values into water content data was tested statistically.Materials and methodsTo develop a predictive equation, T1 values were obtained for tissue-mimicking gelatin samples. 1.5 T MRI was performed using inverse angle phase and an inverse sequence at 37 (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…Less water in the gap indicates formation of bone or at least decreased cartilage and physeal health as cartilage is mainly composed of water. 11 The combined findings in the histological analysis and on MRI, including water content quantification, suggest that autologous cartilage chips in combination with Tisseel ® may be suitable in preventing bone bridges after physeal injuries in the distal femur.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Less water in the gap indicates formation of bone or at least decreased cartilage and physeal health as cartilage is mainly composed of water. 11 The combined findings in the histological analysis and on MRI, including water content quantification, suggest that autologous cartilage chips in combination with Tisseel ® may be suitable in preventing bone bridges after physeal injuries in the distal femur.…”
Section: Discussionmentioning
confidence: 97%
“…T1 and T2-weighted 3D sequences were carried out in addition to T1-weighted quantitative water content sequences. 11 Presence and absence of a bone bridge was determined on MRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, early‐stage OA is associated with loss of proteoglycans, an increase in water content, and changes in the structure of collagen fibers 2 . Yao et al 8 showed the sensitivity of T 1 and T 2 relaxation to early‐stage OA, and it has been shown that T 1 mapping can be used to calculate the water content of the cartilage 9 . In addition to the longitudinal T 1 8 and transverse T 2 relaxation times, 8 the spin‐lattice relaxation in the rotating frame ( T 1 ρ ) can be used to quantify the biochemical changes in cartilage 2,7,10‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Yao et al 8 showed the sensitivity of T 1 and T 2 relaxation to early-stage OA, and it has been shown that T 1 mapping can be used to calculate the water content of the cartilage. 9 In addition to the longitudinal T 1 8 and transverse T 2 relaxation times, 8 the spin-lattice relaxation in the rotating frame (T 1ρ ) can be used to quantify the biochemical changes in cartilage. 2,7,[10][11][12] Both T 1ρ and T 2 have been consistently reported to be elevated with enzymatic cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%